1993
DOI: 10.1002/mus.880161215
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of three median‐to‐ulnar comparative tests in diagnosis of mild carpal tunnel syndrome

Abstract: We studied 193 hands of 113 patients referred for typical carpal tunnel syndrome (CTS). Ninety-five (49%) hands had normal median distal motor latency (< or = 4.2 ms) and normal or borderline sensory conduction velocity from digit 2 stimulation (> or = 45 m/s). In these cases we performed three median to ulnar comparative tests: (1) difference between median and ulnar distal motor latencies recorded from the second lumbrical and interossei muscles (2L-INT); (2) difference between median and ulnar sensory laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
2
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 19 publications
9
73
2
9
Order By: Relevance
“…[6] Measurements of median and ulnar-palmar mixed latencies and median/ ulnar-digit IV differential latencies are most widely used methods. [33,34] Uncini et al [35] found sensitivities of measurements of digit IV-wrist median-ulnar differential latencies, median-ulnar palmar mixed latencies, and L-I method to be 77%, 56%, and 10%, respectively. In a study conducted by Preston et al, [24] the corresponding rates of sensitivity were 91%, 97%, and 88%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Measurements of median and ulnar-palmar mixed latencies and median/ ulnar-digit IV differential latencies are most widely used methods. [33,34] Uncini et al [35] found sensitivities of measurements of digit IV-wrist median-ulnar differential latencies, median-ulnar palmar mixed latencies, and L-I method to be 77%, 56%, and 10%, respectively. In a study conducted by Preston et al, [24] the corresponding rates of sensitivity were 91%, 97%, and 88%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Os métodos comparativos de latências são muito úteis, pois aumentam a sensibilidade eletrodiagnóstica; o paciente serve como seu próprio controle com menor influência da idade, temperatura e distância, além de diminuir problema com neuropatia periférica de base [14][15][16] . Carrol 17 , estudando 50 pessoas normais, encontrou DMR até 0,3 ms para 16-39 anos e até 0,4 ms para 40-82 anos, usando-se 2 DP como limite superior de normalidade, latência medida no pico do PAS e distância variando de 67 a 108 mm (média de 85 mm).…”
Section: Discussionunclassified
“…Zgodnie z zalecanym algorytmem postępowania elektrodiagnostycznego (4) w zależności od wyników badania technikami standardowymi wykonywano także dodatkowe, bardziej czułe testy do oceny przewodnictwa we włóknach czuciowych i ruchowych badanych nerwów (5,6).…”
Section: Materiał I Metodyunclassified